Efektivitas Metode Tutor Sebaya Terhadap Kemampuan Hiragana Siswa SMA Negeri 2 Bukittinggi - isra miyarti; Rita Arni (Universitas Negeri Padang, 2023)
In learning Japanese, there are many students who have difficulty in mastering hiragana. One of the difficulties is the shape of hiragana which looks alike and affects the mastery of beginners in memorizing the forms. Based on the observation of the researcher while conducting educational practice (PPLK) at SMA Negeri 2 Bukittinggi and having interview with the Japanese teacher of the school, the researcher found that students had difficulties in mastering hiragana. It became worse as the students who did not understand preferred to ask their friends instead of their teacher. This caused students’ lack of ability and interest in learning hiragana. Therefore, some methods are needed to increase students’ interest and to make it easier for them to learn hiragana. The use of peer tutoring methods is possible to overcome this problem. The purpose of this study was to determine the effectiveness of the peer tutoring method in improving the students’ ability in reading and writing hiragana in Japanese subject for students from grade XI at SMA Negeri 2 Bukittinggi. This was an experimental quantitative research with the randomized posttest only control group design. The data was taken from a random sample of research class XI IPS 3 and XI IPS 4 which were 64 people in total. Based on the results of the t-test, it can be concluded that the alternative hypothesis (H0) is accepted at a significant level of 5% because tcount >ttabel (2.94>2.00) which means that the students’ ability to read and write hiragana in the experimental class is better from the control class. In the other words, the use of peer tutoring method is effective to improve the students’ ability to read and write hiragana.